(untitled) (Research, Society and Development, 2022)
University students experience experiences of academic life which involves demands of society, among them adapting to the pressures and changes of daily life, in addition to tests and work, load of studies and technological changes in the way of studying, all this can favor the development of depression. The study aimed to compare the prevalence of depression and associated factors in university students of the physical education course practicing and not practicing physical exercise. This is a study with descriptive quantitative analysis. The sample consisted of 200 students, 100 female and 100 male, all university students from HEI. The instrument used in the research was the Beck Depression Inventory (BDI). For data analysis, the Microsoft Office Excel Software was used. The results showed that depression levels were classified as at least (53.0%), followed respectively by mild and moderate (22.0%) and (25.0%). Men are minimally more depressed (61.0%) compared to women (44.0%), while women are more modernly more depressive (29.0%), but the prevalence of severe depression was higher in males (6.0%). Regarding the levels of depression of practicing and non-practicing university students, no association with depression was identified (p = 0.163). It is concluded that physical exercises may be correlated with the release of hormones, play an important role in mood and mental health, showing to be very effective mainly in mild and moderate cases of depression.